Audiovisual Resources and Scientific Method in the initial training of teachers - Risueño Martínez, Jesús J.; Moreno Fuentes, Elena; Hidalgo Navarrete, José (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The present study shows the opinion of preservice teachers in relation to the use of audiovisual resources, more specifically the educational video, to learn the scientific method in the Primary Education stage. A questionnaire is carried out before and after the intervention and the data are compared through the statistical program SPSS v.26. The results show that there are significant differences in aspects such as its usefulness for teachers, inclusion or as a resource to work on environmental education. In addition, there is an increase in the means (not significant) in the other questions raised.